KETERWAKILAN PEREMPUAN SEBAGAI PENYELENGGARAPEMILU MENUJU PESTA DEMOKRASI 2024 - Hajriana Hajriana; Riska Riska (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
In Article 28D of the Constitution of the Republic of 1945 Indonesia paragraph (3) which reads,